1990
DOI: 10.1159/000168080
|View full text |Cite
|
Sign up to set email alerts
|

IgA Nephropathy in Japanese Children and Adults: A Comparative Study of Clinicopathological Features

Abstract: A comparative clinicopathological study was retroscpectively performed in 61 children and 51 adults with IgA nephropathy. Hematuria and/or proteinuria as a chance finding was the most common initial clinical sign, being observed in 82.0% of the children and in 52.9% of the adults. At renal biopsy, hypertension and severe proteinuria were found in 9.8 and 33.3% of the adults and in 0 and 14.8% of the children (both p < 0.05), respectively. Elevations of blood urea nitrogen and serum creatinine were found at thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
30
2
1

Year Published

1993
1993
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 6 publications
3
30
2
1
Order By: Relevance
“…The majority of authors believe that complement activation by the alternative or lectin pathway is important in the pathogenesis of IgAN [1]. However, many studies have shown that a certain proportion of IgAN patients demonstrate the mesangial deposition of C1q [17,18,19,20,21,22,23,25]. This C1q deposition may simply be incidental, and not pathogenic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of authors believe that complement activation by the alternative or lectin pathway is important in the pathogenesis of IgAN [1]. However, many studies have shown that a certain proportion of IgAN patients demonstrate the mesangial deposition of C1q [17,18,19,20,21,22,23,25]. This C1q deposition may simply be incidental, and not pathogenic.…”
Section: Discussionmentioning
confidence: 99%
“…C1q deposition is found in 0 to 45% of patients with IgAN [17,18,19,20,21,22,23,24]. Some studies have found that mesangial C1q deposition is associated with a decrease in eGFR in patients with IgAN [25].…”
Section: Introductionmentioning
confidence: 99%
“…A porcentagem de casos com deposição de C3 confirma a literatura prévia que evidencia tal fração do complemento em mais de 90% das biópsias. 6,40 A porcentagem de deposição de C1q se aproxima de dados dos trabalhos. 41,42 Vale ressaltar que, assim como as lesões histopatológicas, o padrão de deposição à imunofluorescência também é bastante variável ao redor do mundo e que nossos resultados expressam características das biópsias de pacientes do Estado de Minas Gerais.…”
Section: Discussionunclassified
“…Thus, although HSPN patients exhibited more active glomerular lesions in mesangial and endocapillary proliferation, the scoring system suggested by classification was not sufficient to distinguish HSPN from IgAN. Previous studies have shown that IgAN presents with more mesangial proliferation in adult [26][27][28][29][30]. Because a majority of pediatric HSPN and IgAN patients belonged in the highest M score group in present study (Table 4), the M score defined by the Oxford Classification may underscore pediatric IgAN as well as HSPN.…”
mentioning
confidence: 59%
“…The reason for failure of the MEST scheme to differentiate activity of glomerular lesions in HSPN and IgAN may probably relate to the differences in the morphological findings between children and adult with IgAN [26][27][28][29][30]. Younger patients present with significantly more mesangial and endocapillary proliferation.…”
Section: Discussionmentioning
confidence: 99%